Accelerating chemical exchange saturation transfer MRI with parallel blind compressed sensing. Issue 1 (26th August 2018) - She, Huajun; Greer, Joshua S.; Zhang, Shu; Li, Bian; Keupp, Jochen; Madhuranthakam, Ananth J.; Dimitrov, Ivan E.; Lenkinski, Robert E.; Vinogradov, Elena
Abstract : Purpose: Chemical exchange saturation transfer is a novel and promising MRI contrast method, but it can be time‐consuming. Common parallel imaging methods, like SENSE, can lead to reduced quality of CEST. Here, parallel blind compressed sensing (PBCS), combining blind compressed sensing (BCS) and parallel imaging, is evaluated for the acceleration of CEST in brain and breast. Methods: The CEST data were collected in phantoms, brain ( N  = 3), and breast ( N  = 2). Retrospective Cartesian undersampling was implemented and the reconstruction results of PBCS‐CEST were compared with BCS‐CEST and k‐t sparse‐SENSE CEST. The normalized RMSE and the high‐frequency error norm were used for quantitative comparison. Results: In phantom and in vivo brain experiments, the acceleration factor of R = 10 (24 k‐space lines) was achieved and in breast R = 5 (30 k‐space lines), without compromising the quality of the PBCS‐reconstructed magnetization transfer rate asymmetry maps and Z‐spectra. Parallel BCS provides better reconstruction quality when compared with BCS, k‐t sparse‐SENSE, and SENSE methods using the same number of samples. Parallel BCS overperforms BCS, indicating that the inclusion of coil sensitivity improves the reconstruction of the CEST data. Conclusion: The PBCS method accelerates CEST without compromising its quality. Compressed sensing in combination with parallel imaging can provide a valuable alternative to parallel imaging alone for accelerating CEST experiments.